The Indus Seals From Harappa: Study On The Origin Of Raw Material And Production Technology - Ullah, Irfan (2020)
The study of the raw materials used to make the Indus seals, as well as the production technique may give valuable information regarding the technology, economy, and the relation between the Indus societies with the outside world. This thesis examines the Indus seals found in Harappa in order to identify the sources of raw steatite used to make the Indus seals, the techniques employed to harden the soft steatites as well as the carving techniques. The research method ranged from elemental analysis to experimental studies. The elemental study involves analysing steatite samples from Pakistan and Afghanistan, as well as seal samples from Harappa using the XRF and XRD techniques, while the experimental methods included heating, hardness and scratching tests. The results of this study indicated that, in the process of obtaining the steatite sources, residents of Harappa interacted with peoples of northwestern Pakistan and eastern Afghanistan. The result of this study also suggested that the steatite minerals were acquired by the Harappan people from sources outside of the Greater Indus region, which indicated that external trade was a continuous aspect of the socio-economic lives of the residents of Harappa. The experimental archaeology conducted revealed that the bronze tools were used to carve the steatite before these artefacts were being heated.